This preview shows page 1. Sign up to view the full content.
Unformatted text preview: Therefore, we know that ( ) h x will never be greater than x cubed and never be less than negative x cubed. So, we can say: = fx x3 and =gx x3 . We can then calculate the limits of ( ) f x and ( ) g x as x approaches zero from the right. These limits are very simple and we can quickly conclude that → + ( )= limx 0 f x and → + ( )= limx 0 g x . Therefore, according to the squeeze theorem, we can state that → + ( )= limx 0 h x . = ( / ) hx x3cos 1 x = fx x3 limx 0+ → ( )= f x =gx x3 → + ( )= limx 0 g x...
View
Full
Document
This note was uploaded on 11/16/2009 for the course MATH 021 taught by Professor Muralee during the Spring '08 term at Lehigh University .
 Spring '08
 Muralee
 Math, Squeeze Theorem

Click to edit the document details